2010
DOI: 10.1007/s10551-010-0697-5
|View full text |Cite|
|
Sign up to set email alerts
|

You Support Diversity, But Are You Ethical? Examining the Interactive Effects of Diversity and Ethical Climate Perceptions on Turnover Intentions

Abstract: diversity climate, ethical climate, turnover intentions, corporate social responsibility,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 59 publications
7
60
0
5
Order By: Relevance
“…Along with the relationships in clinical settings, diversity of a work group may also affect turnover intentions and decisions (Jones & Harter 2005). Many researchers have examined the impact of perceptions of diversity, generally defined as the extent to which an employee perceives that the organisation values diversity (Kaplan et al 2011, Stewart et al 2011. It is becoming increasingly more evident that in order for diversity initiatives to be successful, the organisation must emphasise the value of the initiative and communicate its fairness (Buttner et al 2010, Stewart et al 2011).…”
Section: Climate Of Diversity and Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the relationships in clinical settings, diversity of a work group may also affect turnover intentions and decisions (Jones & Harter 2005). Many researchers have examined the impact of perceptions of diversity, generally defined as the extent to which an employee perceives that the organisation values diversity (Kaplan et al 2011, Stewart et al 2011. It is becoming increasingly more evident that in order for diversity initiatives to be successful, the organisation must emphasise the value of the initiative and communicate its fairness (Buttner et al 2010, Stewart et al 2011).…”
Section: Climate Of Diversity and Turnovermentioning
confidence: 99%
“…Many researchers have examined the impact of perceptions of diversity, generally defined as the extent to which an employee perceives that the organisation values diversity (Kaplan et al 2011, Stewart et al 2011. It is becoming increasingly more evident that in order for diversity initiatives to be successful, the organisation must emphasise the value of the initiative and communicate its fairness (Buttner et al 2010, Stewart et al 2011). McKay et al (2007 found that across Black, White and Hispanic employees, perceptions of the climate of diversity were negatively related to intention to leave.…”
Section: Climate Of Diversity and Turnovermentioning
confidence: 99%
“…The present study included three dimensions and excluded perceived comfort. McKay et al (2009) Personnel Psychology Diversity climate is employees' shared perceptions of the degree to which a firm is thought to utilize fair employee policies and socially integrate underrepresented employees into the work setting Triana and Garcia (2009) Journal of Organizational Behavior Employee perceptions that the practices of the organization indicate that valuing and promoting diversity is a priority in the organization Gonzalez and DeNisi (2009 Organization Science Diversity climate, is defined as employees' shared perceptions about the extent to which their business unit values diversity by utilizing fair practices and socially integrating all personnel Kaplan et al (2011) Human Resource Management Define the diversity climate as employee perceptions regarding the extent to which individual diversity is valued, integrated into organizational life, and supported through fair employment practices Stewart et al (2011) Journal of Business Ethics Defined as the "degree to which a firm advocates fair human resource policies and socially integrates underrepresented employees" Lauring and Selmer (2011) European Management Review A positive organizational diversity climate refers to group members' attention to issues related to demographic dissimilarities. It can be described as an environment where individuals value and respect the views of those who are different and work actively with a wide variety of individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Job seekers lack information about the company to which they apply and infer companies with high CSR rankings as being fair and reputable [5,6]. In addition, employees of companies that participate actively in CSR have high levels of job satisfaction and organizational identification, resulting in a low turnover of personnel [7,[31][32][33][34]. While prior research focuses on the impact of CSR on employee satisfaction or organizational identification, this study investigates the practical benefits employees can obtain from CSR activities, such as a safer working environment.…”
Section: Literature Reviewmentioning
confidence: 99%